2019
DOI: 10.1002/anie.201912642
|View full text |Cite
|
Sign up to set email alerts
|

Conjugated Copper–Catecholate Framework Electrodes for Efficient Energy Storage

Abstract: A conjugated copper(II) catecholate based metal–organic framework (namely Cu‐DBC) was prepared using a D2‐symmetric redox‐active ligand in a copper bis(dihydroxy) coordination geometry. The π‐d conjugated framework exhibits typical semiconducting behavior with a high electrical conductivity of ca. 1.0 S m−1 at room temperature. Benefiting from the good electrical conductivity and the excellent redox reversibility of both ligand and copper centers, Cu‐DBC electrode features superior capacitor performances with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
123
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 173 publications
(125 citation statements)
references
References 44 publications
2
123
0
Order By: Relevance
“…The obtained hexagonal pore diameter is highly dependent on the size of the ligands and it can reach up to 2.3–2.4 nm when larger ligands with trinaphthalene [12] or truxene [13] cores are used. Ligands based on phthalocyanine, [14] porphyrin, [15] and dibenzo[g,p]chrysene [16] cores are used to construct either tetragonal or rhombic lattice structures depending on D 2 symmetry of the organic linkers. While the coordination of metal ions with ligands in D 6 h symmetry, such as 1,2,3,4,5,6,7,8,9,10,11,12‐perthiolated coronene (PTC), afford 2D c ‐MOFs with Kagome lattice [9b] .…”
Section: Design Synthesis and Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…The obtained hexagonal pore diameter is highly dependent on the size of the ligands and it can reach up to 2.3–2.4 nm when larger ligands with trinaphthalene [12] or truxene [13] cores are used. Ligands based on phthalocyanine, [14] porphyrin, [15] and dibenzo[g,p]chrysene [16] cores are used to construct either tetragonal or rhombic lattice structures depending on D 2 symmetry of the organic linkers. While the coordination of metal ions with ligands in D 6 h symmetry, such as 1,2,3,4,5,6,7,8,9,10,11,12‐perthiolated coronene (PTC), afford 2D c ‐MOFs with Kagome lattice [9b] .…”
Section: Design Synthesis and Characterizationmentioning
confidence: 99%
“…Therefore, high‐resolution transmission electron microscopy (HR‐TEM), X‐ray absorption fine structure (XAFS) spectra, 3D rotation electron diffraction (3D‐RED), 3D electron diffraction tomography (3D‐EDT), and other characterization technologies are also employed for further identifying the structural details of 2D c ‐MOFs (Figure 2). [11b, 14d, 16, 20] …”
Section: Design Synthesis and Characterizationmentioning
confidence: 99%
“…Recently, we reported a high‐performance conductive MOF (i.e. Cu‐DBC) electrode based on a X‐shaped conjugated ligand dibenzo[g,p]chrysene‐2,3,6,7,10,11,14,15‐octaol (8OH‐DBC, Figure 4 a), which showcased an electrical conductivity of ≈1.0 S m −1 [16] . The combination of good electrical conductivity, large SSA, and excellent redox reversibility originated from both DBC ligands and copper centers were beneficial to improving the electrochemical performance.…”
Section: Energy Storagementioning
confidence: 99%
“…In general, benzene [10] and triphenylene [11] based trigonal organic ligands with C 6 or C 3 symmetry tend to form honeycomb lattice with hexagonal channel when coordinated with square-planar atomic metal nodes.T he obtained hexagonal pore diameter is highly dependent on the size of the ligands and it can reach up to 2.3-2.4 nm when larger ligands with trinaphthalene [12] or truxene [13] cores are used. Ligands based on phthalocyanine, [14] porphyrin, [15] and dibenzo-[g,p]chrysene [16] cores are used to construct either tetragonal or rhombic lattice structures depending on D 2 symmetry of the organic linkers.While the coordination of metal ions with ligands in D 6h symmetry,s uch as 1,2,3,4,5,6,7,8,9,10,11,12perthiolated coronene (PTC), afford 2D c-MOFs with Kagome lattice. [9b] Interestingly,Z hu and co-workers have demonstrated that C 6 symmetric ligands,such as benzenehexathiol (BHT) or benzenehexaselenol (BHS), could also form 2D Kagome lattice structures by the coordination with Cu ions.…”
Section: Design Synthesis and Characterizationmentioning
confidence: 99%
“…However, this strategy does not enhance the inherent electrical properties of MOFs but rather decrease the accessible surface areas. [ 5 ] On the other hand, conductive MOFs with high electrical conductivity and permanent porosity have emerged in the past few years, which exhibited improved electrochemical performance in supercapacitors. [ 6 ] Despite the recent achievements, the synthesis of conductive MOFs and their thin‐film fabrication remain tedious.…”
Section: Introductionmentioning
confidence: 99%